Assessing the subjective perception of urban households on the criteria representing sustainable housing affordability - Ezennia, Ikenna Stephen; Hoskara, Sebnem Onal (Elsevier, 2021)
Housing affordability is typically assessed in economic terms, but housing affordability concerns transcend mere housing cost and its relationship to income, to wider issues of social wellbeing and sustainability. New studies on this subject are increasingly recognizing the need for a wider and more holistic understanding of the criteria representing sustainable housing affordability (SHA). Most key authors have embraced this evolution and view the change as positive, and have analyzed industry professionals, academics as well as stakeholders perception along these lines. However, it is not clear whether the views of households align with this since no study has surveyed household opinions. Regarding this, a comprehensive list of 81 potential sustainability performance criteria (SPC) were determined through the review of existing literature. Based on which a questionnaire survey was designed to assess the opinion of households residing in the 26 urban areas of Nigeria on the criticality of these SPC. Through statistical analysis, 30 critical sustainability performance criteria (CSPC) were established. This study posits that at present the housing affordability concerns in urban areas of Nigeria cannot be restrictedly defined by financial attributes. Our findings provide salient information to policymakers and stakeholders that could aid the sustainable delivery of affordable housing programs. (c) 2021 Published by Elsevier B.V. on behalf of African Institute of Mathematical Sciences / Next Einstein Initiative. This is an open access article under the CC BY-NC-ND license ( http://creativecommons.org/licenses/by-nc-nd/4.0/ )
Keywords: Housing affordability; Sustainability; Household perception; Quantitative analysis; Developing countries; Nigeria